Self-Limiting versus Conventional Caries Removal: A Randomized Clinical Trial. (October 2018) - Ali, A.H.; Koller, G.; Foschi, F.; Andiappan, M.; Bruce, K.D.; Banerjee, A.; Mannocci, F.
A single-blind randomized controlled clinical trial in patients with deep caries and symptoms of reversible pulpitis compared outcomes from a self-limiting excavation protocol using chemomechanical Carisolv gel/operating microscope (self-limiting) versus selective removal to leathery dentin using rotary burs (control). This was followed by pulp protection with mineral trioxide aggregate (MTA) and restoration with glass ionomer cement and resin composite, all in a single visit. The pulp sensibility and periapical health of teeth were assessed after 12 mo, in addition to the differences in bacterial tissue concentration postexcavation. Apical radiolucencies were assessed using cone beam computed tomography/periapical radiographs (CBCT/PAs) taken at baseline 0 mo (M0) and 12 mo (M12). In total, 101 restorations in 86 patients were placed and paired subsurface, and deep (postexcavation) dentin samples were obtained. DNA was extracted and bacteria-specific 16S ribosomal RNA gene quantitative polymerase chain reaction was performed. No significant difference was found in bacterial copy numbers normalized to mass of dentin ("bacterial tissue concentration") between the self-limiting (96.3% reduction) and control protocols (97.1%, P = 0.33). The probability of 12-mo success was 4 times (odds ratio [OR] = 4.33; confidence interval [CI], 1.2–15.6; P = 0.025) higher in the self-limiting protocol compared to the control (conventional excavation technique), with pulp survival rates of 73.3% and 90%, respectively ( P = 0.049). Molars had a 4 times higher probability of success compared to premolars (OR, 4.17; CI, 1.17–14.9; P = 0.028), and symptom severity did not statistically predict outcome (OR, 0.41; CI, 0.12–13.9, P = 0.153). CBCT detected significantly more periapical (PA) lesions than PA radiographs at the baseline visit ( P < 0.001). In conclusion, the self-limiting caries excavation protocol under magnification increased pulp survival rate compared to rotary bur excavation (ClinicalTrials.gov NCT03071588).